PROYEKSI KEKRITISAN AIR TAHUN 2021-2035 BERDASARKAN SKENARIO CMIP6 (COUPLED MODEL INTERCOMPARISON PROJECT PHASE 6) DI DAERAH ISTIMEWA YOGYAKARTA - Naim, Asshaffa; Zerlinda, Aurelia; Oktaviani, Malinda Budi; Abidin, Pramuditya Vanesya Putri Febrian; Nurjani, Emilya; Sekaranom, Andung Bayu; Setyaningrum, Etik; Prabowo, Andriyas Aryo (Jurnal Meteorologi dan Geofisika, 2024)
Climate change can lead to an imbalance between water demand and supply, resulting in problems such as water scarcity. To avoid this, a projection of the level of water scarcity is needed. Water scarcity is calculated as the percentage of water demand to water supply. This research aims to determine the level of need, availability, and scarcity of meteorological water. This research uses meteorological water supply obtained through Thornthwaite- Mather water balance calculation from CMIP6 rainfall and temperature projection modeling data in SSP2 and SSP5 scenarios. CMIP6 data was corrected using distribution mapping and average ratios methods to improve the distribution and data values. Water demand indicators are reviewed from three sectors, namely domestic water demands, agricultural water demands, and livestock water demands. The water supply calculation results in Daerah Istimewa Yogyakarta (DIY) show a pattern that fluctuates from year to year during the 2021-2035. Meanwhile, water demand continues to increase along with population growth. The level of water scarcity shows that, overall, DIY is classified as not critical to slightly critical in the SSP2 scenario and not critical to critical in the SSP5 scenario. The difference in the level of scarcity is influenced by socio-economic development and climate change mitigation efforts assumed in each scenario. By knowing the projected level of water scarcity, policymakers are expected to pursue appropriate climate change mitigation measures to actualize the best SSP scenario.